ANALISIS KETAHANAN IKAN LELE DUMBO (CLARIAS GARIEPENUS) YANG DIINFEKSI BAKTERI AEROMONAS HYDROPHILA DENGAN KONSENTRASI BERBEDA: Analysis of The Resilience of Dumbo Catfish (Clarias Gariepenus) Infected With Aeromonas Hydrophila Bacteria With Different Concentrations - Dian Noperta Andrianti; Aryani Rahmawati; I Nyoman Budi Satria; Azhari Tarmizi (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study was to determine the susceptibility of catfish to Aeromonas hydrophila bacteria, and to know the blood picture of catfish infected with Aeromonas hydrophila bacteria. The method used in this study used an experimental method with a Completely Randomized Design (CRD) or Competely Randomized Design (CRD) (Gomez and Gomez, 1984) with 4 (four) treatments and one control each with 3 replications. The results showed that catfish had a strong susceptibility or resistance to Aeromonas hydrophila bacteria. The Lethal Dose value of 50 was 106 cfu/ml, meaning that Aeromonas hydrophila bacteria was able to kill 50% of the catfish population when it was 5.4 x106 cfu/ml. The lowest average red blood cell count was in treatment A, which was 23.89x106 cells/mm3 and the highest in treatment D, which was around 37.5x106 cells/mm3, while the highest and lowest mean total leukocyte counts were 43.07-82.72x103 cells/mm3, still within the range of values. normal. The average hemoglobin concentration was lower than the normal value range in treatment A, which was 6.52 gr% and in treatment D, it was around 12.42 gr%